Effect of the Mobile Phase Acid Additives on Enantioselectivity of Amino Acid Derivative Using Quinine Carbamate Based Chiral Stationary Phase - Fegas, R.; Bensalem, A.; Bettache, Z.; Ouahba, F.; Righezza, M. (Asian Journal of Chemistry, 2010)
Quinine carbamate-type chiral stationary phase has been used for the direct liquid chromatographic enantiomer separation of a wide range of chiral acids. In the present work, we demonstrate that this the chiral stationary phase can also be extended to chiral discrimination of amino acid derivative phthalylvalin using methanol containing different organic acids in mobile phases. The influence of mobile phase composition and enantioselectivity was systematically investigated to gain insight into the overall chiral recognition mechanism.